Answers

2015-06-26T18:37:56+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let first rational number is x = -5/6
, therefore another number will be (8-x) = 8-(- 5/6) = 8 + 5/6 = (48+5)/6 = 53/6
      
0
2015-06-26T18:41:27+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let the other rational number be x 
 Given One of the numbers is -5/6
          Sum of the two numbers is 8
⇒ x + (-5/6) = 8 
⇒ x - 5/6 = 8 
⇒ x = 8 +5/6
⇒ x = (48+5)/6 = 53/6
Check : x - 5/6 = 8 
          ⇒ 53/6 - 5/6 = 8 
          ⇒ 48/6 = 8 
          ⇒ 8 = 8 
Therefore , L.H.S = R.H.S .

0